2018
DOI: 10.1039/c7ra13514a
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of amine-functionalized graphene oxide by microwave-assisted reactions: an outstanding alternative for supporting materials in supercapacitors

Abstract: A simple and straightforward method using microwave-assisted reactions is presented for the functionalization of graphene oxide with aromatic and non-aromatic amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…17,75,76 For carbon nanotubes and similar materials, the specific capacitance in aqueous electrolytes ranges from 50 to 100 F g -1 , which is in good agreement with the results displayed by the materials in this work. Although many studies present the synthesis of carbon materials with much higher capacitance values, like induced verticalaligned carbon nanotubes and polyaniline nanocomposites (403 F g -1 ), 77 reduced graphene oxide films using a standard LightScribe DVD optical drive (276 F g -1 ) 78 and random single walled nanotubes networks (180 F g -1 ), 79 the synthesis procedures of these carbon materials mostly show great difficulties to scale up the production for commercialization of supercapacitors.…”
Section: Resultssupporting
confidence: 80%
“…17,75,76 For carbon nanotubes and similar materials, the specific capacitance in aqueous electrolytes ranges from 50 to 100 F g -1 , which is in good agreement with the results displayed by the materials in this work. Although many studies present the synthesis of carbon materials with much higher capacitance values, like induced verticalaligned carbon nanotubes and polyaniline nanocomposites (403 F g -1 ), 77 reduced graphene oxide films using a standard LightScribe DVD optical drive (276 F g -1 ) 78 and random single walled nanotubes networks (180 F g -1 ), 79 the synthesis procedures of these carbon materials mostly show great difficulties to scale up the production for commercialization of supercapacitors.…”
Section: Resultssupporting
confidence: 80%
“…The stretching frequency appeared at 2200 cm À1 due to the long alkyl chain. 32 The alkyl chain C-H bond vibration appeared at 738 cm À1 . The bond vibration appearing at 1035 cm À1 was associated with an alkyl chain, and the bond appeared at 1052 cm À1 due to the C-O-C stretching frequency.…”
Section: Spectroscopy Studiesmentioning
confidence: 99%
“…[ 15,16 ] GO has been considered as an interesting surface support due to easy functionalization, high surface area, good thermal stability, and better dispersion in water and other organic solvents. [ 17,18 ] The strategy of functionalization on the GO sheets include two approaches such as (a) covalent functionalization of the intercalant by the ring opening of epoxides or chemical conjugation on the secondary OH moieties or coupling on the terminal acid moieties [ 19–22 ] and (b) noncovalent interactions on the surface of GO through van der Waals interactions using aromatic substrates. [ 23–26 ] Spyrou et al have demonstrated the intercalation of organic polycyclic aromatic amines in the GO planes and proved that its interaction with GO differs with the size of the intercalants.…”
Section: Introductionmentioning
confidence: 99%